Functionality of bacterial communities in constructed wetlands used for water purification: influence of root components and seasonality - Huang, Yao; An, Weili; Ning, Tianzhu; Ma, Zhiguang; Li, Yuelin; Liu, Ke; Ji, Lingbo; Liu, Hongxiao; Hui, Dafeng; Ren, Hai (Frontiers in Plant Science, 2025)
IntroductionConstructed wetlands have become crucial ecosystems for the purification of industrial and agricultural water. The health of wetland plants and the efficacy of water purification are strongly influenced by root-associated bacteria. However, our understanding of the functions of bacterial communities in the plant different root components (i.e., rhizosphere, rhizoplane, and endosphere) and their impact on water purification is still limited.MethodsTo address this knowledge gap, we employed high-resolution 16S rRNA deep amplicon sequencing to explore the bacterial community structure and assembly within the root components of three plant species (i.e. Iris ensata, Canna indica, and Hymenocallis littoralis) found in constructed wetlands.ResultsOur findings revealed that the pollutant removal efficiency was higher in the wet season than in the dry season. The specific root compartment, plant species, environmental factors, and seasonality significantly influenced the bacterial composition, diversity and abundance. Across all three plant species, Proteobacteria emerged as the dominant bacterial groups in all root components. The abundance and diversity of bacterial communities exhibited a decline from the rhizosphere to the endosphere, accompanied by an increase in the number of distinctive biomarkers from the rhizosphere to the endosphere. The bacterial composition exhibited significant similarity in the rhizosphere in the dry season and the endosphere in the wet season. Bacterial genes in the rhizosphere-rhizoplane were associated with environmental information processing, transportation and metabolism, while those in the rhizoplane-endosphere primarily handle metabolic processes. The bacterial community positively correlated with total nitrogen content, chemical oxygen demand, and NO4+-N in the dry season, while associated with total phosphorus, total organic carbon, and NO3+-N content in the wet season.DiscussionThe structure and function of the bacterial community within the root rhizoplane-endosphere can serve as indicators of the water purification efficacy of constructed wetlands.